Iconicity in Word Learning and Beyond: A Critical Review - Nielsen, Alan KS; Dingemanse, Mark (Language and speech, 2021)
Interest in iconicity (the resemblance-based mapping between aspects of form and meaning) is in the midst of a resurgence, and a prominent focus in the field has been the possible role of iconicity in language learning. Here we critically review theory and empirical findings in this domain. We distinguish local learning enhancement (where the iconicity of certain lexical items influences the learning of those items) and general learning enhancement (where the iconicity of certain lexical items influences the later learning of non-iconic items or systems). We find that evidence for local learning enhancement is quite strong, though not as clear cut as it is often described and based on a limited sample of languages. Despite common claims about broader facilitatory effects of iconicity on learning, we find that current evidence for general learning enhancement is lacking. We suggest a number of productive avenues for future research and specify what types of evidence would be required to show a role for iconicity in general learning enhancement. We also review evidence for functions of iconicity beyond word learning: iconicity enhances comprehension by providing complementary representations, supports communication about sensory imagery, and expresses affective meanings. Even if learning benefits may be modest or cross-linguistically varied, on balance, iconicity emerges as a vital aspect of language.